2021
DOI: 10.24815/siele.v8i2.18374
|View full text |Cite
|
Sign up to set email alerts
|

Learning from home environment: Academic writing course for EFL undergraduates through Google Classroom application

Abstract: Learning academic writing seems to be a great challenge for most English as a Foreign Language (EFL) students in non-native English-speaking countries, including in Indonesia. During the COVID-19 pandemic, the issue appears to be more challenging where teachers are persuaded to learn from their home environment (LHE). Several online applications are freely available, and one of the most common applications is Google Classroom. However, the use of such application towards the students’ performance and perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 41 publications
6
33
0
3
Order By: Relevance
“…In these circumstances, the motivation of EFL students to write determines their academic writing performances. The more students focus on the performativity of writing (Thomas & Reinertsen, 2019), the better they become in improvement strategies namely feedback condition, reflection assignments, selfefficacy, revisions (Duijnhouwer et al, 2012), and writing assignments (Rosyada & Sundari, 2021). From this point of view, EFL students learn to write independently under the instructor's positive guidance, mentoring roles, and writing tutorials (Munje et al, 2018) resulting in academic writing products or outcomes.…”
Section: Writing Performancementioning
confidence: 99%
“…In these circumstances, the motivation of EFL students to write determines their academic writing performances. The more students focus on the performativity of writing (Thomas & Reinertsen, 2019), the better they become in improvement strategies namely feedback condition, reflection assignments, selfefficacy, revisions (Duijnhouwer et al, 2012), and writing assignments (Rosyada & Sundari, 2021). From this point of view, EFL students learn to write independently under the instructor's positive guidance, mentoring roles, and writing tutorials (Munje et al, 2018) resulting in academic writing products or outcomes.…”
Section: Writing Performancementioning
confidence: 99%
“…It further concluded that the use of technology for learning writing skills was productive and suggested to continue the technology integrated writing classes in future as well. Rosyada and Sundari (2021) aimed to explore the practices of Google classroom in the facilitation of academic writing course to EFL undergraduate students. Data for this explanatory sequential research was collected from 96 participants and analysed by correlating the result data on writing assignments and use of questionnaires.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Sari, 2016;Alvarez, 2020;Mohmmed et al, 2020;Agung, Surtikanti & Quinones, 2020;Maison, Kurniawan, & Anggraini, 2021). Rosyada and Sundari (2021) add that students do not have equal digital literacy and technology support, especially in remote areas. These problems hamper learning quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The supporters of online teaching perceive safety as the top priority. Meanwhile, the con supporters believe in effectiveness and local variations because different institutions have different circumstances and preferences (Rosyada & Sundari, 2021). The government and educational institutions continue their pros and cons arguments in mass media to convince public opinion that their reasons are more logical and applicable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation